Tular Nalar Curriculum to Promote A Culture of Critical Thinking among The Elderly - Astuti, Santi Indra; Satyawati, Niken; Bernadeta, Dwitasari Teteki (Jurnal Vokasi Indonesia, 2024)
In the digital age, fostering a culture of critical thinking is imperative for all societal groups, including the elderly. However, no sufficient effort does appear to resolve the lack of critical thinking among elderly. Facing with this challenge, Tular Nalar program developed unique curriculum which specifically cultivate critical thinking skills among elderly. The designed curriculum become the backbone of capacity buildings which targeted elderly in 38 provinces of Indonesia. This curriculum is accessible to everyone, designed to enhance critical thinking abilities, and enabling individuals, especially the elderly, to identify, analyze, and make rational decisions in filtering information. The paper presented here describes the journey of Tular Nalar in designing the curriculum which employing a qualitative approach research. Three phases of designing curriculum were carried out, started from literature review, focus groups discussions, and pilot projects. During the process, three locations which represent the diversity of Indonesia communities were selected. Padang, Solo, and Ambon become the site of focus groups. Meanwhile, Yogyakarta was chosen for pilot groups to test the curriculum design before finalised for wider audience. As the first study in the country which underlined efforts to construct the curriculum for elderly, the result of the research contributes our understanding about certain issues regarding digital activities as practised by elderly, and how to develop skills and cultivate the culture of critical thinking among them.